A critical assessement of provisions of the Federal Constitution with regard to Federal-State relationship on land law - Awang, Adibah (2008)
This paper examines the relationship between Federal-State government on land law under the Federal Constitution. Under this set up, the Constitution delineates and demarcates the sphere within which these two level of government operates. Basically, land and land-based resources are assigned to the state, meaning that each state government can legislate on land matters. But the Constitution, however, in many instances also allows federal intervention in land matters. In other words, in encouraging diversity in its land law and policy, it also promotes uniformity of law and policy by permitting federal intervention in land and land related matters. As a result, there are more than 200 legislations on land law in Malaysia enacted both or either at federal and state level. Thus, conflict, which ranges from conflict between a federal law and state law to the conflict arising from direct challenges by the state of the federal government’s land policy, is inevitable under this set-up. Hence, this paper reveals the strain and stresses of intergovernmental relations pertaining to land and land-based resources. It finds that land law and policy is increasingly characterised by pragmatic federalism emphasizing collaborative partnerships, adaptable management strategies, and problem and process orientation. The evolving nature of federal-state relations, characterised by expanding federal authorities and increased state capacity, with the recent change in the political scenario, calls for improved coordination & collaboration as to impoverised the land law and land administration system of the country.